Rabies Virus Neutralizing Activity, Safety, and Immunogenicity of Recombinant Human Rabies Antibody Compared with Human Rabies Immunoglobulin in Healthy Adults - ZHANG, Jun Nan; MENG, Ya Juan; BAI, Yun Hua; LI, Yu Feng; YANG, Li Qing; SHI, Nian Min; HAN, Hui Xia; GAO, Jian; ZHU, Li Juan; LI, Shu Ping; ZHANG, Jing; ZHAO, Qin Hua; et al. (Biomedical and environmental sciences, 2022)
Preliminary assessment of rabies virus neutralizing activity, safety and immunogenicity of a recombinant human rabies antibody (NM57) compared with human rabies immunoglobulin (HRIG) in Chinese healthy adults. Subjects were randomly (1:1:1) allocated to Groups A (20 IU/kg NM57), B (40 IU/kg NM57), or C (20 IU/kg HRIG). One injection was given on the day of enrollment. Blood samples were collected on days –7 to 0 (pre-injection), 3, 7, 14, 28, and 42. Adverse events (AEs) and serious AEs (SAEs) were recorded over a period of 42 days after injection. All 60 subjects developed detectable rabies virus neutralizing antibodies (RVNAs) (> 0.05 IU /mL) on days 3, 7, 14, 28, and 42. The RVNA levels peaked on day 3 in all three groups, with a geometric mean concentration (GMC) of 0.2139 IU/mL in Group A, 0.3660 IU/mL in Group B, and 0.1994 IU/mL in Group C. At each follow-up point, the GMC in Group B was significantly higher than that in Groups A and C. The areas under the antibody concentration curve over 0–14 days and 0–42 days in Group B were significantly larger than those in Groups A and C. Fifteen AEs were reported. Except for one grade 2 myalgia in Group C, the other 14 were all grade 1. No SAEs were observed. The rabies virus neutralizing activity of 40 IU/kg NM57 was superior to that of 20 IU/kg NM57 and 20 IU/kg HRIG, and the rabies virus neutralizing activity of 20 IU/kg NM57 and 20 IU/kg HRIG were similar. Safety was comparable between NM57 and HRIG.